Lombroso’s Controversial Legacy at the Interface of Forensic Psychiatry and Odontology: A Critical Analysis of the "Born Criminal" Theory and its Dentofacial Stigmas - Duarte, Marvin Gonçalves; Matos, Alessandra Fátima Britto Barbosa; Filho, José Cardoso de Holanda; Silva, Thiago Luiz de Almeida; Costa, Laís Evelyn Medeiros; Filho, Eudoro de Queiroz Marques; Cunha, Rodolfo Scavuzzi Carneiro da; Filho, Ailton Coelho de Ataíde; Antonino, Manoel Arthur Dias de Oliveira; Silva, Luciano Barreto (Brazilian Journal of Implantology and Health Sciences, 2025)
Objective: To critically reexamine, from a multidisciplinary perspective encompassing Medicine, Psychiatry, and Dentistry, Cesare Lombroso’s work on the “born criminal” theory, with emphasis on dentofacial correlates and their epistemological and social implications. Materials and Methods: A critical literature review was conducted, including a historical analysis of Lombroso’s formulations within the 19th-century epistemological context. His proposed “degenerative stigmata” in dental and facial morphology were detailed and methodologically deconstructed, then contrasted with contemporary scientific knowledge. Results: Findings indicate that Lombroso’s concepts, although scientifically refuted today, significantly influenced medico-legal thought, psychiatry, and the formative stages of forensic dentistry. These ideas were contrasted with modern evidence on psychopathology (including antisocial personality disorder and psychopathy), craniofacial and dental developmental genetics, and the multifactorial etiology of criminal behavior. Furthermore, the ethical and social implications of Lombroso’s biological determinism were discussed, particularly its historical impact on penal policies and the stigmatization of individuals based on physical traits. Conclusion: Lombroso’s theses are scientifically invalidated, yet they hold heuristic value as a paradigmatic case of the dangers of biased interpretations of morphological variations. This study underscores the imperative for continuous methodological and ethical rigor at the interface of biology, medicine, psychiatry, and dentistry.